Fuzzy control of compliance force actuator module - Dou, Zi (2018)
The project provides a solution of accurate and efficient force control of compliance actuator of robot arm by using Series Elastic Actuator Model with treating the motor as a velocity source to the elastic element, rather than as a torque source. PID controller is used to achieve fast rise time and little overshoot. A research on the improved PID model accomplished with the use of MATLAB®/SIMULINK®, and the PID parameters fine tune process will be provided. Furthermore, this project develops the model applied Arduino program, which functionally well for the customized compliance actuator with ROS (Robotics Operating System) communication. Last but not least, as the muscle stiffness can be considered as disturbance that would affect the control’s accuracy and efficiency, it also be taken into consider for further improvement. In this project, the muscle stiffness report will be generated by analyzing the useful data from customer’s massage testing.